Why I March? - Faiza Ahmed (International Journal on Women Empowerment, 2019)
The tale is as old as time, women have been fighting for their rights for centuries. Their lives have always been restricted, and the rationale is unelucidated. They constantly face inequality in the society, be it in the western world or more conservative countries of the world. It never came easy for women; they not only had to raise voice for the basic rights which their counterparts are already endowed with. In 1913, first big rally was arranged by Woman Suffrage Procession, it was the first big public meeting in Washington D.C. for sanction voting for women in the entire country of United States of America. The March was attended by many women and sadly the March was attacked by police of Washington State, injuring around 300 women. The state police also mentioned “There would be nothing like this happen if you would have stayed at home”. Even though in some states of USA, women were permitted to vote since 1869 however, the entire country did not get the right to vote until 1919, which was a big achievement for the women globally. Women of USA and Europe have had many public gatherings to increase awareness about importance of being an equal citizen in the society.